2021
DOI: 10.1080/02640414.2021.1883311
|View full text |Cite
|
Sign up to set email alerts
|

The positive association between perceived parental responsiveness and self-esteem, anxiety, and thriving among youth rugby players: A multigroup analysis

Abstract: The purpose of this study was to examine the association between young players' perception of mother's and father's responsiveness with their self-esteem, anxiety (i.e., worry), and thriving (i.e., positive affect, vitality, and life satisfaction). In total, 314 male British rugby players with a mean age of 16.23 years (SD = 0.26) completed the study in two phases: n = 124 (first dataset), and n = 192 (second dataset). Participants trained on average 3.14 times/week (SD = 0.94) and had been involved in rugby f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Aligning with previous research exploring parent's self-reported positive behaviours ( 16 , 17 ), the current study suggests athletes perceive a similarly high prevalence of positive parent behaviours in sport. Given that positive parent behaviour in sport has been identified to improve youth self-esteem ( 25 ), life skill development ( 26 ), and reduce anxiety ( 27 ), this finding is promising, and we should be encouraging parent positive behaviours to continue. Indeed, research has shown that youth found more enjoyment in their sporting experience when there was active and positive parental involvement in the form of encouragement from the sidelines ( 28 ).…”
Section: Discussionmentioning
confidence: 98%
“…Aligning with previous research exploring parent's self-reported positive behaviours ( 16 , 17 ), the current study suggests athletes perceive a similarly high prevalence of positive parent behaviours in sport. Given that positive parent behaviour in sport has been identified to improve youth self-esteem ( 25 ), life skill development ( 26 ), and reduce anxiety ( 27 ), this finding is promising, and we should be encouraging parent positive behaviours to continue. Indeed, research has shown that youth found more enjoyment in their sporting experience when there was active and positive parental involvement in the form of encouragement from the sidelines ( 28 ).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it seems that selfesteem does improve with the social support network, but it is necessary to determine with what type of sources it improves (Galante & Ward, 2017;Pedrosa et al, 2012;Park et al, 2020). In fact, participating in a competitive sport can improve the self-esteem of adolescent athletes and it is also likely that this engagement strengthens athletes' relationships with their family (Kang et al, 2015;Mastrogianni et al, 2020;Rouquette et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of sport psychology, social support is an external resource that helps athletes cope better with stress (Katagami & Tsuchiya, 2016). And, in some studies it is evident that athletes' perceptions of parental support are related to their sport performance mediated by self-esteem (Rouquette et al, 2021). In Gabana et al (2017) study conducted with Olympic athletes and their coaches note that the provision of support is personally and professionally rewarding and the athletes appeared highly dependent on their support providers.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on young Spanish rugby players (15-19 years old) identified the importance of the models offered by parents and their role/influence in playing the game in the early years, but also draws attention to the low popularity in the media [63], a situation similar to the state of rugby in Romania. The parents of young rugby players are advised to constantly talk to them about their wishes and needs and to provide them with the support they need [64]. The study of 314 boys in England (average age of 16.23 years) showed positive associations between parents' receptivity to youth prosperity/vitality and negative associations between parents' receptivity to athletes' anxiety and anxiety levels before and after competitions, mediated by self-esteem.…”
Section: Discussionmentioning
confidence: 99%